Structural Integrity Analysis of Reinforced Concrete Hotel Wing Accommodating Elevated Swimming Pool - Shofi Mahilla Yuzkia ’Azyzi; Januar Sasongko (Darul Yasin Al Sys, 2026)
Although reinforced concrete hotel design has received considerable attention, research addressing the interaction between vertical public live loads and elevated swimming pool hydrostatic loads on asymmetric wing structures in hilly topographies remains limited. This study aims to evaluate the structural integrity, load distribution, and section capacity of a hotel wing's upper structural system (slabs, beams, columns) under gravity, fluid, and environmental loads per Indonesian National Standards (SNI). A quantitative descriptive computational evaluation design was employed, selecting upper structural elements through purposive sampling. Data from archival documentation-shop drawings, material specifications (f'c, fy), and planning records—were analyzed via 3D finite element modeling in SAP2000 v26 to evaluate internal forces (Mu, Pu, Vu) and demand-to-capacity ratios (D/C) under ultimate load combinations (U = 1.2D + 1.6L + 1.2F) per SNI 1727:2020, SNI 1726:2019, and SNI 2847:2019. Findings indicate effective load transfer with demand-to-capacity ratios within safe limits (D/C ≤ 1.0). Critical force concentrations-maximum flexural moment (Mu,33), axial compression (Pu), and shear (Vu,22)-occur at Frame Object 57 due to eccentric hydrostatic loading combined with public live loads. These findings advance understanding of multi-axial load transfer in elevated leisure facilities. The conclusion highlights the necessity of precise hydrostatic modeling and section verifications for modified commercial buildings. Practical implications offer guidance for engineers and hotel management in structural safety assurance, while theoretical contributions enrich structural auditing literature. Future research should explore full-coupled soil-structure interaction (SSI) and nonlinear dynamic pushover analysis under severe seismic excitation.